Розроблення фірмового стилю для гуртка учнівського лісництва загальноосвітньої школи І-ІІІ ступенів села Годомичі - Левчук, Анна; Мина, Жанна (Видавництво Львівської політехніки, 2020)
This article describes the need for a corporate identity for student forestry. The essence of the concept of “corporate style” is revealed. Peculiarities of student forestry activity are investigated.
Keywords: фірмовий стиль; брендбук; стиль школи; логотип; послуги; учнівське лісництво; школа